A Randomized Treatment Study to Compare the Efficacy of Repeated Nerve Blocks with Cognitive Therapy for Control of Chronic Head and Neck Pain - George Gale; David Nussbaum; Peter Rothbart; Beverley Hann; Van Leung; Gillian Kanetz (Pain Research and Management)
This prospective study compared the efficacy of two antinociceptive modalities: nerve blocks and cognitive therapy. A consecutive series of patients receiving nerve block therapy was invited to take part in a six-week randomized comparison of nerve blocks and cognitive therapy. Sixty-eight of 102 patients approached by telephone agreed to participate. Patients attended eight weekly treatment sessions. Baseline and seven weekly sets of values were recorded. The principal measure of outcome was the Pain on a Visual Analogue Scale (VAS). The secondary measures were the Hospital Anxiety and Depression Scale, and the Activities of Daily Living as measured on the Primary Care Cooperative Information Project/World Organization of National Colleges, Academies (COOP-WONCA) scale. Within the first week, one patient of 34 in the nerve block group withdrew and 12 of 34 in the cognitive therapy group withdrew from the study. After seven weeks, 33 patients in the nerve block group remained in the trial, but only 21 patients completed the questionnaires. Four of 22 patients in the cognitive therapy group completed the trial and their questionnaires. Mean VAS scores in the nerve block group dropped slightly during treatment. Mean VAS scores in the cognitive therapy group rose during the trial. However, the mean VAS score of the remaining four in the last week was below the initial group mean. Patients who had been receiving nerve blocks proved willing to remain in the study if allocated to the nerve block group and unwilling to remain in the cognitive therapy group while foregoing their accustomed treatment.